Guru Berprestasi Sumber Daya Manusia Pengembang Mutu Pendidikan Indonesia - Rusi Rusmiati Aliyyah; Widyasari Widyasari; Didi Mulyadi; Sri Wahyuni Ulfah; Siti Rahmah (Journal Of Administration and Educational Management (ALIGNMENT), 2019)
The purpose of this research is to describe the selection and process coaching that is given to outstanding national-level teachers at Al Irsyad Al Islamiyyah Bekasi West Java. Using approach qualitative with the case study method. Data collected through observation, interviews and documentation. Data analysis techniques data using reduction, data presentation, and concluding. The results of the study stated that the selection of outstanding teachers was carried out in stages starting from the level of the education unit, sub-district, levels district/municipality, provincial and national. Conclusion, outstanding teacher selection consists of academic, administrative and special requirements. Prospective teachers are given guidance and training by education stakeholders ranging from school principals in units education, KKG, education offices, local government, supervisors, LPMP, Higher Education, and P4TK. Keywords: Selection, Guidance, Outstanding Teachers